2019
DOI: 10.1108/jhtt-12-2017-0141
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of technology applications in the restaurant industry

Abstract: Purpose This study aims to examine the utilization of Front of House (FOH) and Back of House (BOH) technology applications in different types of US restaurants along with their level of IT management and explore the importance of these technology applications to restaurant operations. Design/methodology/approach Survey data were collected from 500 randomly selected restaurant technology managers who subscribe to Hospitality Technology Magazine. The sample group represented 67,299 restaurant units. Data analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 85 publications
1
32
0
2
Order By: Relevance
“…Furthermore, it was found that H2 was accepted whereby H2: There was a significant association between innovation and performance. The result was consistent with the previous findings (Koutroumanis, 2011;Cavusoglu, 2015;Firoid & Croitoru 2015) which showed technological innovations possessed significant effect on restaurant.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, it was found that H2 was accepted whereby H2: There was a significant association between innovation and performance. The result was consistent with the previous findings (Koutroumanis, 2011;Cavusoglu, 2015;Firoid & Croitoru 2015) which showed technological innovations possessed significant effect on restaurant.…”
Section: Resultssupporting
confidence: 92%
“…This suggests that it is urgent to shed light on the drivers of m-wallet adoption as the country looks to shift to a cashless society [ 11 ]. This is especially true in the restaurant industry, a sub-industry under the hospitality industry [ 12 ]. Given that the restaurant industry is essential for travellers [ 13 ] and affects the Malaysian economy significantly [ 14 ], this study focuses solely on the restaurant industry.…”
Section: Introductionmentioning
confidence: 99%
“…This would, ultimately, enhance their competitive advantage compared to those who are accepting cash as the only payment method. However, the low utilisation of m-wallet by Malaysian users in the restaurant industry, a sub-industry under the hospitality industry [ 12 ], must be taken note of [ 10 ]. As such, this study could provide insights and findings that could help the stakeholders in the hospitality industry to develop strategies in encouraging the use of m-wallet.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are hundreds of valuable publications for both cases, we can mention only some of them here (e.g. Andaleeb and Conway, 2006, Ryu and Lee, 2017or Barlan-Espino, 2017 for the traditional applications and Pantelidis, 2009, Koutroumanis, 2011or Cavusoglu, 2019 for the latter), since they are beyond the scope of this abstract. For those who are interested in more comprehensive study, we can refer to Demicco et.al, 2015. As the dissemination and the power of technology increases every single day, encountering with the phenomena becomes inevitable.…”
Section: Part 5: Education and Trainingmentioning
confidence: 99%